2020
DOI: 10.3390/v12050491
|View full text |Cite
|
Sign up to set email alerts
|

ACE2: The key Molecule for Understanding the Pathophysiology of Severe and Critical Conditions of COVID-19: Demon or Angel?

Abstract: Recently, the SARS-CoV-2 induced disease COVID-19 has spread all over the world. Nearly 20% of the patients have severe or critical conditions. SARS-CoV-2 exploits ACE2 for host cell entry. ACE2 plays an essential role in the renin-angiotensin-aldosterone system (RAAS), which regulates blood pressure and fluid balance. ACE2 also protects organs from inflammatory injuries and regulates intestinal functions. ACE2 can be shed by two proteases, ADAM17 and TMPRSS2. TMPRSS2-cleaved ACE2 allows SARS-CoV-2 cell entry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
177
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(202 citation statements)
references
References 54 publications
0
177
1
11
Order By: Relevance
“…2 ACE2 acts as a membrane receptor in this process, which also involves interactions with other effectors, such as type 2 transmembrane serine proteases. 3 The ACE2 protein plays an important role as a negative effector in the renin angiotensin aldosterone system, converting angiotensins I and II into angiotensins 1-9 and 1-7, respectively. Angiotensins 1-9 and 1-7 have vasodilatory and anti-inflammatory effects, among other actions, thereby antagonizing the classic hypertensive and inflammatory effects of angiotensin II.…”
Section: The Role Of Angiotensin-converting Enzyme Type 2 (Ace2)mentioning
confidence: 99%
See 1 more Smart Citation
“…2 ACE2 acts as a membrane receptor in this process, which also involves interactions with other effectors, such as type 2 transmembrane serine proteases. 3 The ACE2 protein plays an important role as a negative effector in the renin angiotensin aldosterone system, converting angiotensins I and II into angiotensins 1-9 and 1-7, respectively. Angiotensins 1-9 and 1-7 have vasodilatory and anti-inflammatory effects, among other actions, thereby antagonizing the classic hypertensive and inflammatory effects of angiotensin II.…”
Section: The Role Of Angiotensin-converting Enzyme Type 2 (Ace2)mentioning
confidence: 99%
“…Angiotensins 1-9 and 1-7 have vasodilatory and anti-inflammatory effects, among other actions, thereby antagonizing the classic hypertensive and inflammatory effects of angiotensin II. 2,3 Infection by SARS-CoV-2 causes death of cells rich in ACE2 receptors and cellular internalization of a proportion of these receptors, ultimately causing a reduction in circulating ACE2 activity. 4 This results in angiotensin II activity predominating over activity of angiotensins 1-7 and 1-9.…”
Section: The Role Of Angiotensin-converting Enzyme Type 2 (Ace2)mentioning
confidence: 99%
“…Consequently, ACE2 serves as a double‐edged sword playing dual roles of a demon as well as an angel. It not only opens the doors for SARS-CoV-2 as a receptor but also helps protects the body from severe pathological changes (Cheng, Wang et al 2020 ; Xiao, Sakagami et al 2020 ; Yan, Xiao et al 2020 ). In the current COVID-19 outbreak, ACE2 is a topic of pronounced interest and several studies are being carried out to assess the interaction of SARS-CoV-2 with ACE2, the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…conducted a molecular docking experiment between CQ and ACE2 and found that CQ binds to ACE2 with low binding energy and forms a stable complex system (Abdelli et al, 2020). Studies have shown that ACE2 is a type I membrane-bound glycoprotein composed of 805 amino acids, mainly distributed in vascular endothelial cells, alveolar and renal tubular epithelial cells, and profoundly expressed in tissues such as heart, kidney, retina, and gastrointestinal tissue (Xiao et al, 2020). Flow cytometry and immunoprecipitation studies have shown that during alveolar epithelial cell infection with SARS virus, CQ and HCQ can prevent the binding of viral S protein to ACE2 by disrupting ACE2 terminal glycosylation (Brufsky, 2020;Vincent et al, 2005).…”
Section: Introductionmentioning
confidence: 99%